Nurse Managers' Leadership Styles in Finland - Soili Vesterinen; Marjo Suhonen; Arja Isola; Leena Paasivaara (Hindawi Limited, 2012)
Nurse managers who can observe their own behaviour and its effects on employees can adjust to a better leadership style. The intention of this study was to explore nurses' and supervisors' perceptions of nurse managers' leadership styles. Open-ended interviews were conducted with 11 nurses and 10 superiors. The data were analysed by content analysis. In the study, six leadership styles were identified: visionary, coaching, affiliate, democratic, commanding, and isolating. Job satisfaction and commitment as well as operation and development work, cooperation, and organizational climate in the work unit were the factors, affected by leadership styles. The nurse managers should consider their leadership style from the point of view of employees, situation factors, and goals of the organization. Leadership styles where employees are seen in a participatory role have become more common.